Confessions and Denials When Guilty and Innocent: Forensic Patients' Self-Reported Behavior During Police Interviews - Volbert, Renate; May, Lennart; Hausam, Joscha; Lau, Steffen (Frontiers in Psychiatry, 2019)
Several self-report studies together with analyses of exoneration cases suggest that suspects with mental impairment are especially prone to making false confessions. The present study asked 153 forensic patients in Germany about their behavior during suspect interviewing by the police. Self-reported ground truth of guilt and innocence was asked for, thereby taking into account that the risk of false confession is present only if a person has ever been interviewed when innocent. Indeed, surveys of samples including suspects who have never been interviewed when innocent may therefore underestimate the risk of false confessions. In the present study, all patients reported having been interviewed previously when guilty, and almost two-thirds (62%; n = 95) indicated that they had also been interviewed at least once when innocent. Participants stated that they remained silent while interviewed significantly more often when guilty (35%) compared to being interviewed when innocent (15%). This corroborates results found in laboratory research indicating that the right to remain silent is waived more often by innocent than guilty suspects. Out of all 95 participants who were ever interviewed when innocent, 25% reported having made a false confession on at least one occasion. This result is in line with previous international research showing a high percentage of false confessions among suspects with mental impairment.